Influence of Physical Exercise on Advanced Glycation End Products Levels in Patients Living With the Human Immunodeficiency Virus - Rodrigues, Karine Lino; Borges, Juliana Pereira; Lopes, Gabriella de Oliveira; Pereira, Evelyn Nunes Goulart da Silva; Mediano, Mauro Felippe Felix; Farinatti, Paulo; Tibiriça, Eduardo; Daliry, Anissa (Frontiers in Physiology, 2018)
Introduction: Combined antiretroviral therapy (cART) used to treat acquired immunodeficiency virus (HIV) induces a number of adverse effects, such as insulin resistance and dyslipidemia, which ultimately increases the cardiovascular risk. Advanced glycation end products (AGEs) have been implicated in the etiology of cardiovascular diseases, diabetes and other chronic diseases. It is known that physical exercise improves the lipid profile, insulin resistance and reduces the risk of cardiovascular diseases. However, the impact of physical exercise on AGE levels in HIV-infected patients has not been so far investigated. Therefore, this study compared AGEs levels in people with and without HIV and verified the effect of physical training on serum AGE levels. Methods: Participants were initially assigned into three groups: healthy control (CTL, n=35), physically inactive HIV-infected (In-HIV, n=33) and physically active HIV-infected (Ac-HIV, n=19). The In-HIV group underwent physical training for 3 months, consisting of 60-min sessions of multimodal supervised exercise (aerobic, resistance and flexibility) with moderate intensity (50-80% heart rate reserve), performed 3 times/week. AGEs were measured in serum by fluorescence spectrometry. Results: At baseline, serum AGEs fluorescence level was significantly higher in inactive HIV-patients when compared to controls or active HIV-patients (In-HIV: 0.93 ± 0.08 vs controls: 0.68 ± 0.13 and Ac-HIV: 0.59 ± 0.04 A.U.; P < 0.001). Triglycerides were also higher in In-HIV than CTL (182.8 ± 102 vs 132.8 ± 52.3 mg/dL; P<0.05). Waist circumference was lower in Ac-HIV, compared to In-HIV and controls (83.9 ± 10.4 vs 92.9 ± 13.5 and 98.3 ± 12.4, respectively; P<0.05). Body mass, fasting blood glucose, LDL, HDL, and total cholesterol were similar between groups. After training, AGE levels decreased (Baseline: 0.93±0.08 vs 3 months follow-up: 0.59 ± 0.04 AU; P < 0.001), no further difference being detected vs. CTL or Ac-HIV. Conclusion: HIV-infected patients under cART exhibited elevated AGEs levels compared to healthy individuals and physically active patients. Short-term aerobic training of moderate intensity counteracted this condition.